Analyzing the effect of the COVID-19 vaccine on Parkinson’s disease symptoms - Sabat, Revati; Dayton, Orrin L.; Agarwal, Amit; Vedam-Mai, Vinata (Frontiers in Immunology, 2023)
Background Parkinson’s Disease (PD) is one of the most common neurodegenerative diseases. PD has recently received more attention by researchers in the midst of the COVID-19 pandemic. Objective Yet to be researched is the effect of the COVID-19 vaccines on PD patients. Several PD patients are still hesitant to the vaccine due to this unaddressed fear. The purpose of this study is to address this gap. Methods Surveys were administered to PD patients 50 years and older at UF Fixel Institute who received at least one dose of the COVID-19 vaccine. Survey questions included patients’ severity of PD symptoms before and after the vaccine and extent of worsening PD symptoms post-vaccination. After three weeks of collecting responses, the data was analyzed. Results 34 respondents were eligible for data consideration because they fell within the age range being studied. A total of 14 respondents out of 34 (41%, p=0. 0001) reported that their PD symptoms worsened after the COVID-19 vaccine to some extent. Conclusion There was strong evidence of worsening of PD symptoms post COVID-19 vaccination, however it was mostly mild and limited to a couple of days. The worsening had statistically significant moderate positive correlation with vaccine hesitancy and post-vaccine general side effects. A possible causative mechanism of PD symptom worsening using existing scientific knowledge would be stress and anxiety associated with vaccine hesitancy and the extent of post-vaccine general side effects (fever, chills, pain), likely via simulating a mild systemic infection/inflammation the latter already established causes of PD symptom worsening.